Substance Use and Violent Victimization: Evidence from a Cohort of >82,000 Patients Treated for Alcohol and Drug Use Disorder in Denmark - Seid, Abdu Kedir (Journal of interpersonal violence, 2022)
Although the association between substance use and violence has been well established, knowledge on predictors for violent victimization of individuals treated for alcohol use disorder (AUD) or drug use disorder (DUD) is lacking. Using Goldstein?s tripartite conceptual framework, this study examines the relationship between substance use and violent victimization. Data were derived from national registers on persons aged between 15 and 75 years, living in Denmark, and admitted for AUD or DUD treatment during 2006-2016 (n = 82,767). Rates of new incidence of violent victimization were estimated per 10,000 person years for the patient cohort, and for an age- and gender-matched control group of 492,397 people with no history of treatment for drug and alcohol problems. The incidence of victimization for the AUD/DUD sample was 145.6 per 10,000 person years and 5.4 per 10,000 person years for the comparison cohort. Results of multivariate Cox regression on specific types of substance use supported Goldstein?s psychopharmacological and economic compulsive models of victimization, but not the systemic model. Gender-stratified results showed that the use of cannabis and methadone was associated with victimization in women treated for AUD and DUD. Patients with a non-Western background were more likely to experience victimization than Danish patients. The study highlights the strong association between substance use disorder and victimization, and the important role that service providers play in addressing the high levels of victimization experienced by patients with AUD or DUD.